Extractive Spectrophotometric Determination of Molybdenum using p-Chloroisonitroso Acetophenone Hydrazone - Lokhande, R.S.; Agashe, A.P.; Hundiwale, D.G. (Asian Journal of Chemistry, 2010)
Separation technique like solvent extraction can be advantageously employed for the determination of metals at low concentration in micrograms using spectrophotometric methods. Hydrazoxine has been used for the extraction and spectrophotometric determination of metals at trace level as well as for the studies of transition metals in complex form. In the present paper, solvent extraction technique has been used to develop methods for the separation and spectrophotometric determination of Mo(VI) with p-chloroisonitroso- acetophenone hydrazone (HICAPH) prepared as per procedure reported by Dey using p-chloroisonitroso acetophenone. Complex formed with p-chloroisonitroso acetophenone hydrazone was extracted into chloroform from aqueous solution in the pH range 8 to 8.5. The ,absorption maxima was also tried for the extracted species and Beer's law was also studied for its applicability. In this, interference from the foreign ion has also been examined.